Post-Colonial Issues of Modern Russian Literature - Shafranskaya, Eleonora (Respectus Philologicus, 2015)
The article discusses the controversial reception of the terms “colonial” and “post-colonial”, used in the modern studies of postcolonial discourse. The author provides the analysis of the works of the modern Russian literature that focus on the post-colonial issues, or, to be more exact, the post-orientalistic judgment of the Soviet and imperial problems (Andrey Volos’s prose, Dina Rubina, Arkan Kariv, Larisa Bau, Sukhbat Aflatuni, Adel Khairov whose works contain the elements of traditional Orientalism as well as post-Said Orientalism). This article provides an overview (with arguments and illustrative material of interdisciplinary nature) of the specificity and techniques of the modern post-colonial Russian literature. In particular, it analyses the metaphor of stagnation – lethargic hospital – and the reception of enantiosemy; considers the image of the place genius loci, which is leaving or have already departed from the real world not physically but mentally, and the former locus of the former Soviet empire; places the emphasis on the post-colonial reflection of the modern novelists, a post factum wish to understand the reasons of post-imperial problems.
Keywords: colonial Russian literature; post-colonial Russian literature; modern Russian prose; Sukhbat Aflatuni; Larisa Bau; Andrey Volos; Arkan Kariv; Dina of Rubin; Adele Khairov; lethargic hospital; enantiosemy; genius loci